Perlindungan Hukum Bagi Pelaku Usaha Penyedia Air Bersih Terhadap Konsumen Yang Telat Bayar - Ade Winanengsih; Muhammad Luthfi Radian (LPPM Universitas Ekasakti Padang, 2024)
Buying and selling is part of the community’s activites to meet their needs as living beings. The need for clean water is the main source for humans to sustain their life. Nowadays, there are still many needs for clean water that do not have legal certainty within the scope of the regulations in force in Indonesia. Many consumers and clean water service providers still suffer losses. The purpose of this study is to analyze the legal protection for clean water service providers against consumers who are late in making payment. The research method used in this study is an empirical normative approach, which combines normative legal approaches with the addition of various empirical elements.